Effects of low-order surface vacancy on extinction spectra of localized surface plasmon resonance - Kwak, Sang Kyu (2013)
In this study, we demonstrate the use of discrete dipole approximation (DDA) approach to estimate the influenced of low order surface vacancies on the localized surface plasmon resonance that is in the range of di-to squarevacancy. Gold rectangular nanoprism was chosen as a model for the simulation due to its recent unique surface plasmon resonance property. We have found that when the concentration of vacancy is kept in the lowest with unity in number, the apparent fluctuations in extinction spectra are observed and captured and the fluctuation is depending on the wavelength of incident light, the order of vacancy, and the arrangement of vacancy. Also, the agglomeration of vacancy enhances fluctuation behavior of the extinction spectra over the wavelength of interest. Diagonally arranged vacancy scatters light the most. Considering that most studies using DDA have only considered perfect nanoprisms in comparison with experimental results, this vacancy treatment might be an imminent factor to be included for future DDA calculations of plasmonic nanomaterials.